2017
DOI: 10.1108/lm-08-2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

Librarians and compensation negotiation in the library workplace

Abstract: Purpose -The purpose of this paper is to report on survey results from a study about librarians' experience with compensation (salary and benefits) negotiation in the library workplace in order to provide data that will inform professional discourse and practice.Design/methodology/approach -A primarily quantitative survey instrument was administered via Qualtrics Survey Software and distributed through listservs and social media channels representing a range of library types and sub-disciplines. The survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Examining responses by gender showed that 53% (n=49) of women and 78% (n=14) of men negotiated. While this trend is consistent with the findings of other studies (Farrell & Geraci, 2017;Greig, 2008), the pool of male participants was limited.…”
Section: Negotiation Response By Years Of Experience Prior To Offersupporting
confidence: 91%
“…Examining responses by gender showed that 53% (n=49) of women and 78% (n=14) of men negotiated. While this trend is consistent with the findings of other studies (Farrell & Geraci, 2017;Greig, 2008), the pool of male participants was limited.…”
Section: Negotiation Response By Years Of Experience Prior To Offersupporting
confidence: 91%
“…Similarly, employers use prior salary information as an indication of a candidate's worth (Farrell et al, 2017). According to Marginal Productivity Theory, each individual gets paid based on his or her contribution to the employer's revenue (Pressman, 2014).…”
Section: Need Of Evidencementioning
confidence: 99%